Queijo de leite ovino : uma alternativa para o pequeno produtor rural - Vaz, Adil Knackfuss; Ide, Gilberto Masashi; dos Santos , Domingos Silvestre; Pedemonte, Fernando Cannella (Agropecuária Catarinense, 2002)
PDF